The cinva program and the community action (2008)
This article approaches to the subject of urban planning in the Bogotá 50’s scenario from the experience of the Inter-American Center of House and Urban Planning (CINVA). It points out to the auto-construction project of houses proposed by this program as a part of a planning model that, submitted to the intervention of international programs, tried to approach from integral perspective main problems of the Colombian urban surroundings happening at the second half of XX century.